If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 54 = 2x + -102 Reorder the terms: 54 + 8x = 2x + -102 Reorder the terms: 54 + 8x = -102 + 2x Solving 54 + 8x = -102 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 54 + 8x + -2x = -102 + 2x + -2x Combine like terms: 8x + -2x = 6x 54 + 6x = -102 + 2x + -2x Combine like terms: 2x + -2x = 0 54 + 6x = -102 + 0 54 + 6x = -102 Add '-54' to each side of the equation. 54 + -54 + 6x = -102 + -54 Combine like terms: 54 + -54 = 0 0 + 6x = -102 + -54 6x = -102 + -54 Combine like terms: -102 + -54 = -156 6x = -156 Divide each side by '6'. x = -26 Simplifying x = -26
| 4x^2-16x-91=-7 | | 7+4x=-25 | | 17+p=-14 | | 2x-8=3x-102 | | 5x-11x+6=0 | | 7=0.5m | | 1x+56=-6x+119 | | 3p-6=3p-p | | 5e=4.5 | | -163=7x+6(-3x-18) | | X+4(1-x)=-17 | | 9-4y-12=-10y-25 | | 8+2p=2 | | 1234326567898780-098543=g-12345678756 | | 14k+5=k+14 | | 9x+11=4+5x+2x | | (3+-9x)+9x=3 | | -8=28-5x | | -20-15y=-17 | | 2(2x+3y)(3x-4y)= | | 10g-3x+10=8 | | 2x-8=3x-120 | | -15.5=2.5+3.5(d-7) | | -6-2x=32 | | 2s+3s= | | 9f=8u+7c-21k | | 27+24x=26x-35 | | -15t^2+90t-120=0 | | -4+x/3=-5 | | -9.5=-38 | | 2v^2+3=0 | | 10x+7=3(3x+7) |